Pengaruh Kompetensi Fasilitator Terhadap Partisipasi Masyarakat Program Sekolah Orang Tua Hebat di Kota Surabaya - Clara Aritonang; Heryanto Susilo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2026)
Community participation is a key determinant of the success of non-formal education programs, including the Sekolah Orang Tua Hebat (SOTH) program designed to enhance parents' capacity in child-rearing. Variations in community participation levels were found in Lidah Wetan Village, Surabaya, presumably related to differences in facilitator competence. This study aimed to determine the effect of facilitator competence on community participation in the SOTH program. A quantitative approach with simple linear regression analysis was used, involving all 58 active participants as the total sample. Data were collected using a closed questionnaire with a four-point Likert scale, tested for validity using Pearson Product Moment correlation and reliability using Cronbach's Alpha. The results showed that facilitator competence has a positive and significant effect on community participation, with a t-value of 2.036 > t-table 2.003 and significance value of 0.046 < 0.05. The regression equation is Y = 17.295 + 0.230X, with R² = 0.069, meaning facilitator competence contributes 6.9% to community participation. It is recommended that program organizers conduct continuous training and supervision on andragogy facilitation, participatory communication, and professional development to increase active community participation.